Bacterial Diversity, Chemical Composition, and Fermentation Quality of Alfalfa-Based Total Mixed Ration Silage Inoculated with Lactobacillus reuteri and Lentilactobacillus buchneri - Anum Hanif; Fuhou Li; Samaila Usman; Neha Sheoran; Xusheng Guo (Fermentation)
This study examined the effects of lactic acid bacteria (LAB) from extremely cold environments on the bacterial diversity, chemical composition, and fermentation quality of alfalfa-based TMR silage. The TMR was treated with Lactobacillus reuteri A4-2 (Lr A4-2) and Lentilactobacillus buchneri 9-2 (Lb 9-2) at an application rate of 1.0 × 105 cfu/g fresh material, respectively, and the control received the same volume of distilled water. The TMR was ensiled for 7, 15, 30, 60, and 210 days. The Lr A4-2 treatment produced higher lactic acid (62.53 g/kg DM at 210 days) and maintained a diverse bacterial community throughout the ensiling compared with the control and Lb 9-2 treatment. The Lb 9-2 treatment increased acetic acid (51.42 g/kg DM at 210 days) and formed a distinct bacterial community profile. The 16S rRNA sequencing revealed a shift from initial Weissella dominance to Lactobacillus-dominated communities across the treatments by day 210. Alpha diversity indices decreased over time, with Lr A4-2 treatment maintaining higher diversity. Principal coordinate analysis demonstrated significant temporal shifts in bacterial community composition among treatments (p < 0.01). The results suggest that different heterofermentative LAB strains modulated the fermentation and microbial balance in alfalfa-based TMR silage in different ways.